Senam Lansia Di RSJD Dr. Amino Gondohutomo - Widya Ervianta; Lilik Sigit Wibisono; Fitratun Najizah; Auliya Rahma Putri; Panji Satria Wiguna (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
The elderly are an age group that is prone to falls. The purpose of this service is to detect the risk of falling in the elderly and provide assistance in balance training as an effort to prevent the risk of falling in the elderly. Falls occur due to unintentional loss of balance resulting in failure of postural stability, or unexpected and sudden changes resulting in a position landing on the floor. Associated risk factors include current health status (living in the community, nursing home, hospital, frail or active state), diseases suffered (diabetes, hip fracture, stroke) and general changes related to aging (decreased balance, coordination, muscle strength, visual impairment, etc.). The output targets to be achieved are in the form of publications in accredited national journals and copyright for videos of community service activities. The method used is a fall risk detection examination using. Elderly gymnastics is a series of regular, directed, and planned movements carried out with the intention of improving the functional abilities of the body. Reporting from the Panti Rapih Hospital page, this activity is carried out regularly and with movements that are not too heavy.